Development of good quality of yogurt in terms of texture, flavor, food value and low cost and determining the fat percentage of milk and yogurt - Modhu, Anila Labonnya (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.